Haemogregarines from western Palaearctic freshwater turtles (genera Emys, Mauremys) are conspecific with Haemogregarina stepanowi Danilewsky, 1885 - Dvořáková, Nela; Kvičerová, Jana; Papoušek, Ivo; Javanbakht, Hossein; Tiar, Ghoulem; Kami, Hajigholi; Široký, Pavel (Parasitology, 2014)
The majority of Haemogregarina species have been based on the morphology of their erythrocytic stages and supposed strict host specificity. The quantity of species with a limited number of overlapping diagnostic traits has led to a considerable mess in haemogregarine taxonomy and significant synonymy. We analysed host specificity, intra- and interspecific variability, evolutionary relationships, and the distribution of the type species of the genus Haemogregarina--H. stepanowi. The morphology of blood stages and 18S rDNA sequences of this haemogregarine from four western Palaearctic hard-shelled freshwater turtles (Emys orbicularis, Mauremys caspica, Mauremys leprosa and Mauremys rivulata) were compared with Haemogregarina balli. Additional sequences of 18S rDNA of Haemogregarina-like isolates collected from three species of African hinged terrapins (genus Pelusios) were used to enlarge the dataset for phylogenetic analyses. Thirteen sequences (1085 bp) of Haemogregarina representing all four western Palaearctic turtle species were identical, corresponding to H. stepanowi, which is closely related to the Nearctic species H. balli. In our analyses, Haemogregarina spp. constituted a monophyletic clade sister to the genus Hepatozoon. Haemogregarina stepanowi possesses a wide distribution range from the Maghreb, through Europe, Turkey and the Middle East to Iran. We consider that the genus Haemogregarina has a low host specificity crossing the family level of its vertebrate hosts and that its distribution is likely to be linked to the vector and definitive host--the leech.
Keywords: Host Specificity; Leeches; infekce přenášené vektorem; sekvence nukleotidů; RNA ribozomální 18S; Coccidiosis; DNA, Ribosomal; kokcidióza; Phylogeny; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; Female; Host-Parasite Interactions; zvířata; sladká voda; hostitelská specificita; sekvenční analýza DNA; Disease Vectors; ženské pohlaví; pijavice; Base Sequence; Fresh Water; fylogeneze; želvy; Turtles; ribozomální DNA; Animals; Eucoccidiida; RNA, Ribosomal, 18S; interakce hostitele a parazita